2015
DOI: 10.1002/path.4587
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelioma cells breaking bad: loss of integrin α7 promotes cell motility and poor clinical outcomes in patients

Abstract: Mesothelioma is a disease of pleural cells lining the lungs which is often caused by exposure to asbestos. The molecular mechanism(s) that regulate the transformation of pleural mesothelioma cells to a migratory and malignant phenotype are unclear. In recent work published in this journal, Laszlo et al performed a set of elegant experiments to identify a key molecular mechanism that may explain the aggressive nature of this disease. Using patient-derived mesothelioma cells with high versus low migratory activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Decreased integrin expression has also been correlated with cancer progression. In mesothelioma, reduced expression of ITGA7 was associated with promoter methylation and was identified as an important mechanism for the aggressive migratory transformation of mesothelioma [121,122]. Similar results have also been seen with a2b1 in breast cancer, and a6b4/ a6b1 in oesophageal carcinoma [59].…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionsupporting
confidence: 61%
See 1 more Smart Citation
“…Decreased integrin expression has also been correlated with cancer progression. In mesothelioma, reduced expression of ITGA7 was associated with promoter methylation and was identified as an important mechanism for the aggressive migratory transformation of mesothelioma [121,122]. Similar results have also been seen with a2b1 in breast cancer, and a6b4/ a6b1 in oesophageal carcinoma [59].…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionsupporting
confidence: 61%
“…An early sequencing study demonstrated a positive association between mutations in subunit a7 (encoded by ITGA7 gene), identified in 57% of prostate cancers, and increased cancer recurrence [120]. In mesothelioma, reduced expression of ITGA7 was associated with promoter methylation and was identified as an important mechanism for the aggressive migratory transformation of mesothelioma [121,122]. Decreased integrin expression has also been correlated with cancer progression.…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionmentioning
confidence: 99%
“…ITGA7, which encodes the adhesion molecule integrin α7, was selected since integrins have been described as playing an important role in cancer progression [35][36][37] as well as normal cell processes [38][39][40] through ECM binding [41,42] and transduction of cellular signaling [43][44][45]. Although the expression of ITGA7 in glioblastomas correlates to poor prognosis [35], the clinical significance of ITGA7 expression is controversial in other malignancies [35][36][37][46][47][48][49][50][51], and its role and expression in AML have not yet been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, evidence has been provided that temsirolimus non-responsiveness is associated with altered integrin α5 and β3 expression levels, coupled to a functional change in the integrin molecules, driving tumor cells towards high motility [ 5 ]. Novel data point to the integrin subtype α7 (ITGA7) as a potential tumor biomarker [ 6 , 7 ] and it has been speculated that ITGA7 could serve as a highly specific diagnostic and therapeutic target [ 8 , 9 ]. Still, it is not yet clear whether temsirolimus induced drug resistance contributes to changes in ITGA7 expression or whether alterations of this receptor type can modify invasive properties of RCC cells.…”
Section: Introductionmentioning
confidence: 99%